A Human TSC1 Variant Screening Platform in Gabaergic Cortical Interneurons for Genotype to Phenotype Assessments - Wundrach, Dean; Martinetti, Luis E.; Stafford, April M.; Bilinovich, Stephanie M.; Angara, Kartik; Prokop, Jeremy W.; Crandall, Shane R.; Vogt, Daniel (Frontiers in Molecular Neuroscience, 2020)
The TSC1 and TSC2 genes are connected to multiple syndromes from Tuberous Sclerosis Complex (TSC) to Autism Spectrum Disorder (ASD), with uncertainty if genetic variants cause all or subsets of phenotypes based on the location and type of change. For TSC1, few have addressed if non-TSC associated genetic variants have direct contributions to changes in neurological genotype-to-phenotype impacts, including elevated rates of ASD and seizures. Dominant variants cause TSC, yet TSC1 has many heritable variants not dominant for TSC that are poorly understood in neurological function, with some associated to ASD. Herein, we examined how some missense variants in TSC1, R336W, T360N, T393I, S403L and H732Y, impacted the development of cortical inhibitory interneurons, cell-types whose molecular, cellular and physiological properties are altered after loss of mouse Tsc1. We found that most missense variants complemented phenotypes caused by loss of Tsc1, i.e. increased cell size and several cell intrinsic physiological properties. However, distinct variants, particularly S403L showed deficits in complementing an increase in parvalbumin levels and exhibited smaller amplitude after hyperpolarizations. Overall, these data show that subtle phenotypes can be induced by some TSC1 missense variants and provide an in vivo system to better assess TSC1 variants’ neurological impact.